Advances and Challenges on Management of Gastrointestinal Stromal Tumors - Mei, Lin; Du, Wei; Idowu, Michael; von Mehren, Margaret; Boikos, Sosipatros A. (Frontiers in Oncology, 2018)
Gastrointestinal stromal tumors (GISTs) originate from interstitial cells of Cajal and account for over 5,000 newly diagnosed cases in the United States. The discovery of activated KIT and PDGFRA mutations and introduction of imatinib revolutionized the treatment strategy and opened up the new era of target therapy for solid tumors. Although surgery remains the primary modality of treatment for curative purpose, almost half of the patients experienced disease recurrence. Tailoring (neo)-adjuvant treatment with imatinib is ongoing to meet the need for an effective therapy. Currently, two drugs (sunitinib and regorafenib) have obtained FDA approval for GISTs after imatinib failure. However, most of the patients eventually progress due to primary or secondary resistance. Deeper understanding of the molecular mechanisms will guide us to develop personalized strategies in the future. Discussion in this review includes current standard management, the most recent advances and multiple ongoing clinical trials with different approaches. This review will provide further steps to be taken to conquer refractory disease.